Luminescence Properties of SiO2@Eu(phen-Si) (sulphoxide) Core-Shell Nanometer Composite - Li Yi-Lian; Li Wen-Xian; Zheng Yu-Shan (MATEC Web of Conferences, 2018)
A novel ternary europium complex Eu(Phen-Si)·(H2L)2·(ClO4)3·6H2O was prepared using (phen)-N-(CONH(CH2)3Si(OCH2CH3)3)2 (Phen-Si) as the first ligand and 2-carboxyphenyl carboxymethyl sulphoxide (H2L) as the second ligand. The corresponding different thickness core-shell structure SiO2@Eu(phen-Si)·L nano composites were synthesized, with silica spheres as core, ternary europium complex (Eu(Phen-Si)·(H2L)2·(ClO4)3) as shell. The ternary europium complex has been characterized by element analysis, molar conductivity, and IR spectra. The SiO2@Eu(phen-Si)·L core-shell structure composite was characterized by TEM and IR spectra. Core-shell structure composites exhibited stronger fluorescence properties than that of the ternary europium complex. The emission intensity of the two core-shell composites was 1.79, 3.99 times stronger than the ternary europium complex, respectively. The fluorescence lifetime of the core-shell structure composites were longer than the ternary europium complex.